(untitled) (Tanzania Journal for Population studies and Development, 2009)
For almost four decades, a significant amount of Finnish aid to Tanzania has been spent supporting various projects in the two southern regions of Mtwara and Lindi. Beginning mid-1990s up to mid-2005, the Finns implemented a program known as Rural Integrated Project Support (RIPS), designed to empower rural communities in Mtwara and Lindi to own and control the development process. Based on fieldwork in villages in Mtwara and Lindi, this article sets out to examine the extent to which the Finnish intervention in participatory-development planning has resulted in the empowerment of the rural populations. The article argues that, rather than leading to empowerment of the rural communities, the RIPS program reproduced and consolidated the power of the government bureaucracy. These findings challenge the assumed relationship between participatory approaches and the reality of peoples’ empowerment.